THE INFLUENCE OF STRAY KIDS AS BRAND AMBASSADOR AND KOREAN WAVE THROUGH BRAND IMAGE AS MEDIATING VARIABLE ON CONSUMERS’ PURCHASE DECISION OF ‘NACIFIC’ FRESH HERB SERUM IN JAKARTA - Aprilliani Desylvia Rahma Puteri; Ngatno Ngatno; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2025)
NACIFIC is a cosmetic brand from South Korea known for its high-quality skincare products with one of its flagship products, namely Fresh Herb Serum. Along with the growing interest in Korean beauty products, NACIFIC has gained popularity in the international market, including in Indonesia. However, from 2019 to 2023 NACIFIC’s sales of Fresh Herb Serum in Jakarta has been fluctuated. If the Company does not make innovations to increase sales, then the Company will suffer losses and threaten its existence. This study aims to find out the influence of Stray Kids as a Brand Ambassador and Korean Wave on Purchase Decision through Brand Image as a Mediation Variable. The type of research used is explanatory research using data collection techniques in the form of questionnaires. The sample used in this study was 100 people with the technique of non-probability sampling of purposive sampling type. The sample criteria in this study were respondents who were domiciled in Jakarta City, had bought NACIFIC fresh herb serum product at least 1 time, and were aged over 17 years old. Data processing is carried out with SPSS for Windows version 25.0. The research results show that Brand Ambassador and Korean Wave have a positive and significant influence on Purchase Decision, both directly and indirectly through Brand Image. The relationship of Brand Image as a mediating variable is a partial mediation for both independent variables. Suggestions that can be given to NACIFIC, include to create interesting content on social media platforms, as well as collaborating with popular celebrities as brand ambassadors which can help increase the visibility of brand image.